Causes and consequences of facultative sea crossing in a soaring migrant. (24th February 2020) - Becciu, Paolo; Rotics, Shay; Horvitz, Nir; Kaatz, Michael; Fiedler, Wolfgang; Zurell, Damaris; Flack, Andrea; Jeltsch, Florian; Wikelski, Martin; Nathan, Ran; Sapir, Nir
Abstract: Studying the causes and consequences of route selection in animal migration is important for understanding the evolution of migratory systems and how they may be affected by environmental factors at various spatial and temporal scales. One key decision during migration is whether to cross 'high transport cost' areas or to circumvent them. Soaring birds may face this choice when encountering waterbodies where convective updrafts are weak or scarce. Crossing these waterbodies requires flying using energetically costly flapping flight, while circumventing them over land permits energetically cheap soaring. We tested how several atmospheric factors (e.g. wind, thermal uplift) and geographic, seasonal and state‐related factors (sex and age) affected route selection in migrating white storks Ciconia ciconia . We used 196 GPS tracks of 70 individuals either crossing or circumventing the north‐easternmost section of the Mediterranean Sea, over Iskenderun Bay in southern Turkey. We found that westward and southward winds promoted a cross‐bay journey in spring and autumn, respectively, acting as tailwinds. Also, overall weaker winds promoted a sea crossing in spring. Sea crossing was associated with flapping flight and higher values of overall dynamic body acceleration and resulted in higher ground speed than travel over land. The combined environmental conditions and the effects of route selection on movement‐related energy costs and speed were likely responsible for an increase in the time spent flying and distance travelled of migrating storks that decided to cross the bay during spring. Notably, daily travel distances of spring migrants crossing the bay were 60 km longer than those of land‐detouring birds, allowing them to reach their destination faster but likely incurring a higher energetic flight cost. No such benefit was found during autumn. Our findings confirm that atmospheric conditions can strongly affect bird route selection. Consequently, migration timing, speed and movement‐related energy expenditure differed considerably between the two migratory seasons and the two route choices, highlighting a time‐energy trade‐off in the migration of white storks. A free plain language summary can be found within the Supporting Information of this article. Abstract : A free plain language summary can be found within the Supporting Information of this article.